Characterization of scintillator screens under irradiation of low energy 133Cs ions. (1st February 2022) - Toledo-Garrido, J.J.; Galdon-Quiroga, J.; Viezzer, E.; Birkenmeier, G.; Olevskaia, V.; Balden, M.; Garcia-Lopez, J.; Jimenez-Ramos, M.C.; Rodriguez-Ramos, M.; Anda, G.; Videla-Trevin, M.; Garcia-Munoz, M.; et al.
Abstract: An imaging heavy ion beam probe (i-HIBP) diagnostic, for the simultaneous measurement of plasma density, magnetic field and electrostatic potential in the plasma edge, has been installed at ASDEX Upgrade. Unlike standard heavy ion beam probes, in the i-HIBP the probing (heavy) ions are collected by a scintillator detector, creating a light pattern or strike-line, which is then imaged by a camera. Therefore, a good characterization of the scintillator response is needed. Previous works focused on the scintillator behaviour against irradiation with light ions such as hydrogen and alpha particles. In this work we present the characterization of several scintillator screens — TG-Green (SrGa2 S4 :Eu2 + ), YAG-Ce (Y3 Al5 O12 :Ce3 + ) and P11 (ZnS:Ag) — against irradiation with 133 Cs + ions, in an energy range between 5 and 70 keV and ion currents between 10 5 and 10 7 ions/(s·cm 2 ). Three main properties of the scintillators have been studied: the ionolumenescence efficiency or yield, the linearity and the degradation as a function of the fluence. The highest yield was delivered by the TG-Green scintillator screen with > 8·10 3 photons/ion at 50 keV. All the samples showed a linear response with increasing incident ion flux. The degradation was quantified in terms of the fluence F1/2, which leads to a reduction of the emissivity by a factor of 2. TG-Green showed the lowest degradation with F1/2 = 5.4·10 14 ions/cm 2 . After the irradiation the samples were analyzed by Scanning Electron Microscopy (SEM), Rutherford Backscattering Spectrometry (RBS) and Particle Induced X-ray Emission (PIXE). No trace of Cs was found in the irradiated regions. These results indicate that, among the tested materials, TG-Green is the best candidate for the i-HIBP detector.